INFLUENCE OF FINAL CARBONIZATION TEMPERATURE IN THE PHYSICAL AND CHEMICAL CHARACTERISTICS OF THE JATOBÁ(Himenea courbaril L.) CHARCOAL - TRUGILHO, Paulo Fernando; da SILVA, Dimas Agostinho (Scientia Agraria, 2001)
The purpose of this study was to verify the relationship between the pyrolisis and physical and chemical characteristics of the jatobá (Himenea courbaril L.) charcoal. It was also studied the behavior of the heartwood and sapwood with respect to the carbonization process and the effects of its chemical composition to the heat of combustion of the fuelwood. In addition, some physical-chemical characteristics of the wood charcoal were analyzed. The results suggest that the difference between the heartwood and sapwood charcoal is caused by differences anatomical structure and chemical composition of the materials. It was also determined that the charcoal specific gravity pass over a minimum point at 660º C for both heartwood and sapwood. It was not observed any change in the fixed yield carbon of charcoal obtained from heartwood and sapwood with the increase of the final carbonization temperature. Finally, it was determined a positive relationship between the heat of combustion of the wood charcoal with its fixed carbon and ash contents and negative relationship with the volatile material contents.